2017
DOI: 10.17508/cjfst.2017.9.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation time and mix ratio on some nutritional qualities of the dry mixture of maize and sorghum powder (Ogi)

Abstract: Indexing p. 1  Editorial Bord p. 1  Guide for Authors p. 3  Manuscript preparation p. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is commonly used as a weaning food for toddlers. Pap (akamu) also serve as a breakfast meal for adults and children [5,6]. Sick people are usually fed with pap because it digests quickly [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is commonly used as a weaning food for toddlers. Pap (akamu) also serve as a breakfast meal for adults and children [5,6]. Sick people are usually fed with pap because it digests quickly [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Pap (akamu) also serve as a breakfast meal for adults and children [5,6]. Sick people are usually fed with pap because it digests quickly [4,6]. In local markets, ogi is usually displayed as a wet cake covered with transparent polythene bags or leaves [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature abounds with information on the production of ogi from maize (Bolaji, Adenuga-Ogunji, & Abegunde, 2017a;Okara & Lokoyi, 2012), millet (Inyang & Idoko, 2006;Olawale, Oyeleke, Akinro, & Olakunle, 2012), sorghum (Adelekan & Oyewole, 2010;Apotiola, 2013), or the combination of two or more of these cereals (Eke-Ejiofor, 2018; Odewole et al, 2017). However, despite being one of the most important cereal crops in the world, as well as the most economically important crop in developing countries (Ajala & Gana, 2015), there is dearth of information on the suitability of rice for ogi production.…”
Section: Introductionmentioning
confidence: 99%
“…It is a semi-finished food cooked into smooth, free flowing creamy or thin porridge. 11 Influence of fermentation duration, mix ratio, biopreservation of cereals during production of either fermented paste or flour have been studied by some researchers. 9,12,13 Many studies have reported on supplementation of cereals with different legumes, because of the absence of lysine in cereal grains which is abundant in legumes, 12 the use of roots and tubers such as potato in supplementing cereal grains has not gained much popularity in production of complementary foods.…”
Section: Introductionmentioning
confidence: 99%